Immune escape and immune camouflage may reduce the efficacy of RTS,S vaccine in Malawi - Sundos Khan; Matthew Parrillo; Andres H. Gutierrez; Frances E. Terry; Leonard Moise; William D. Martin; Anne S. De Groot (Taylor & Francis Group, 2020)
The RTS,S/AS01 malaria vaccine will undergo a pilot vaccination study in sub-Saharan Africa beginning in 2019. RTS,S/AS01 Phase III trials reported an efficacy of 28.3% (children 5-17 months) and 18.3% (infants 6-12 weeks), with substantial variability across study sites. We postulated that the relatively low efficacy of the RTS,S vaccine and variability across sites may be due to lack of T-cell epitopes in the vaccine antigen, and due to the HLA distribution of the vaccinated population, and/or due to 'immune camouflage', an immune escape mechanism. To examine these hypotheses, we used immunoinformatics tools to compare T helper epitopes contained in RTS,S vaccine antigens with Plasmodium falciparum circumsporozoite protein (CSP) variants isolated from infected individuals in Malawi. The prevalence of epitopes restricted by specific HLA-DRB1 alleles was inversely associated with prevalence of the HLA-DRB1 allele in the Malawi study population, suggesting immune escape. In addition, T-cell epitopes in the CSP of strains circulating in Malawi were more often restricted by low-frequency HLA-DRB1 alleles in the population. Furthermore, T-cell epitopes that were highly conserved across CSP variants in Malawi possessed TCR-facing residues that were highly conserved in the human proteome, potentially reducing T-cell help through tolerance. The CSP component of the RTS,S vaccine also exhibited a low degree of T-cell epitope relatedness to circulating variants. These results suggest that RTS,S vaccine efficacy may be impacted by low T-cell epitope content, reduced presentation of T-cell epitopes by prevalent HLA-DRB1, high potential for human-cross-reactivity, and limited conservation with the CSP of circulating malaria strains.